Functional Near-infrared Spectroscopy Reveals the Compensatory Potential of Pre-frontal Cortical Activity for Standing Balance in Young and Older Adults. (1st January 2021) - St George, Rebecca J.; Hinder, Mark R.; Puri, Rohan; Walker, Eliza; Callisaya, Michele L.
Highlights: The function of pre-frontal cortical activity during standing balance is unclear. A dual-cognitive task loaded cortical resources during increasing balance difficulty. Younger people showed increasing PFC activity with increasing balance difficulty. Older people showed a limit in PFC activity beyond which they exhibited instability. Pre-frontal cortical activity can help stabilize balance in a 'top–down' manor. Abstract: Recent evidence suggests increased activity of the pre-frontal cortex (PFC) is associated with sensorimotor disturbances of standing balance. Here we manipulate sensorimotor inputs and concurrently load cognitive resources in order to investigate the functional role of PFC activity during standing balance, and how this changes with healthy ageing. Healthy younger ( n = 24; mean age = 20.8 years) and older ( n = 25; mean age = 70.6 years) adults maintained balance while sensorimotor inputs were manipulated by removing vision, reducing the base of support, and reducing proprioceptive feedback. To load cognitive resources, each balance condition was undertaken alone or simultaneously with a cognitive task (dual-task). Functional near infrared spectroscopy (fNIRS) measured PFC activity and a force-plate measured postural sway. When comparing dual-tasks relative to single balance tasks (dual-task effect), at lower levels of balance task demand, the older adults exhibited increased PFC activity and similar levels of postural sway. However, at higher levels of balance task demand, a limit to PFC activity was observed and postural sway became more unstable in older adults. In contrast, for younger adults at higher levels of balance task demand, the dual-task effect resulted in an increase in PFC activity and postural sway was not unduly affected. These results suggest that PFC activity is compensating for sensorimotor deficits to maintain stability, and that a cognitive resource limit is reached for easier balance tasks in older people compared to younger people. These results suggest that increasing cortical capacity in older people may improve their balance.